Augmented Reality (AR) and Java Application Development for Geometry Learning Medium - Andy Satria (Journal Mathematics Education Sigma [JMES], 2024)
In the context of mathematics education, specifically in the domain of solid geometry, conventional instructional media, such as textbooks, have been the norm. However, their efficacy is constrained by the reliance on two-dimensional representations, impeding students' comprehension of the concepts conveyed by educators. Many students encounter difficulty in recognizing three-dimensional geometric shapes, resulting in disengagement and a lack of focus. The incorporation of spatial concepts can be significantly enhanced by employing Java-based desktop applications capable of converting tangible objects into three-dimensional graphics. This technological approach offers a more creative means of identifying mathematical spatial formulas. For instance, through the utilization of mobile device cameras, users can practically visualize three-dimensional representations of spatial structures. The presentation of geometric shapes in three dimensions facilitates accelerated learning, allowing students to swiftly comprehend, memorize, and apply formulas accurately to each solid shape. The interactive learning media, based on augmented reality and Java Desktop, attained an expert validation score of 84.1%, indicating a classification of excellence. Furthermore, design experts validated the media with a score of 80%, qualifying it as excellent. Learning media experts provided a validation score of 81.5%, categorizing the augmented reality and Java Desktop-based interactive learning media as excellent. Group testing results indicated a noteworthy 86.7%, falling within the excellent category.